Navigating Intersectionality: Gender, Disability, and Ethnic Equity in Secondary Education - Tanami; Yusuf Isla (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the intersectionality of gender, disability, and ethnicity in the pursuit of educational equity within secondary education contexts. Using a qualitative case study approach, the research examines how these overlapping identities influence students’ access to learning opportunities, treatment within school systems, and overall academic experiences. Data were collected through interviews with students, teachers, and administrators, as well as classroom observations and document analysis in three diverse secondary schools. The findings reveal that while policies often address issues of equity in isolation, students experience multiple, layered forms of marginalization that are frequently overlooked in implementation. Schools with inclusive practices grounded in intersectional awareness were more effective in addressing these complexities, fostering student engagement and improving academic and social outcomes. The study highlights the need for an educational framework that integrates intersectionality to better support equity efforts, particularly in multicultural and diverse learning environments.